Revisiting the Concept of Stability in the General Theory of Crime - Nofziger, Stacey (Crime & delinquency, 2020)
The general theory proposes that self-control exerts a relatively stable effect on behaviors across the life course. Most studies have examined the stability of self-control itself, rather than whether it leads to persistent patterns of offending that differ between low and high self-control groups. This article examines this alternative idea of stability by tracing patterns of offending over time. Using data from the National Longitudinal Survey of Youth—Child and Young Adult Data, we find that the level of childhood self-control predicts deviance in every age group. The patterns of offending indicate there are stable differences, with low self-control leading to involvement in a greater range of deviant behavior at every age. The theoretical and policy implications of this stability are discussed.